Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/e20060405
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectricity and Thermodiffusion in Magnetic Nanofluids: Entropic Analysis

Abstract: An analytical model describing the thermoelectric potential production in magnetic nanofluids (dispersions of magnetic and charged colloidal particles in liquid media) is presented. The two major entropy sources, the thermogalvanic and thermodiffusion processes are considered. The thermodiffusion term is described in terms of three physical parameters; the diffusion coefficient, the Eastman entropy of transfer and the electrophoretic charge number of colloidal particles, which all depend on the particle concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…15 for D m (H) in Ref. 45 , including derivatives of the NP's chemical potential with respect to temperature. Note that here the Eastman entropy of transfer of the NP's is supposed independent onH.…”
Section: In-field Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 for D m (H) in Ref. 45 , including derivatives of the NP's chemical potential with respect to temperature. Note that here the Eastman entropy of transfer of the NP's is supposed independent onH.…”
Section: In-field Resultsmentioning
confidence: 99%
“…Finally we present the in-field anisotropy of the diffusion coefficient D m and of the Soret coefficient S T . The field-dependence of S T is here adjusted with a mean field model 45 , similar to the one previously developed to describe the in-field D m -anisotropy 46,47 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that at the other extreme condition, the Soret equilibrium, when the thermodiffusive motions of all particles are completed, the Seebeck coefficient Se st only depends on the redox couple's reaction entropy [27] (here, it is assumed that the Eastman entropy of transfer of redox species and that of counterions are small, and that the ionic strength at the hot and cold electrodes are not greatly modified)…”
Section: Production Of Thermoelectric Voltage In Liquid Thermogalvanimentioning
confidence: 99%
“…In ionic, aqueous ferrofluids, the magnitude and the direction of S T are known to depend strongly on the ionic environment; i.e., the pH level, the counterion types and concentrations, the effective charge number of individual particles, etc. Despite such complex natures, the existing theoretical models [23][24][25][26][27] have been successfully applied to describe experimental observations [28][29][30][31] in the case of colloidal suspensions prepared in weak electrolytes. The link between the thermodiffusive motion and the resulting Seebeck potential has also been verified in ferrofluids based on weak electrolytes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…When submitted to a gradient of temperature rT , ionic nanoparticles (NPs) dispersed in a polar solvent are subjected both to the Ludwig-Soret e↵ect [1], which induces a gradient of volume fraction r and a Seebeck e↵ect [2,3], which induces an electric field E. This can be used for potential thermoelectric applications in terms of heat recovery [4][5][6][7][8][9][10]. In stationary conditions, both r and E are proportional to rT and the NPs migrate either towards the cold region or towards the hot region depending on the sign of their Soret coe cient S T , given (at high dilution) by r = S T rT .…”
Section: Introductionmentioning
confidence: 99%